An Assignment of Local Service Delivery and Local Governments in Kenya - World Bank (Washington, DC, 2013)
The report examines the local government sector in Kenya, the reform and decentralization process, and the dynamics of local service delivery. The report is organized in three parts. The first, traces the broad contours of the reform process in Kenya: the inter-governmental system, local government and key local service sectors (such as water, roads, education, and health), and the macro reform processes (such as the public sector reforms, and the Kenya Constitution Review). The second part, reviews the existing systems for local service delivery, including aspects such as institutional arrangements, planning and financing for local services, and the structure, and finances of local governments. The third part focuses on a synthesis of key issues in the reform process, and discusses the strategic directions for both the Bank, and the Department of International Development (DFID), regarding future support to the Government of Kenya for improvements in local service delivery, and related local government reform.